Thermal insulation of YSZ and erbia-doped yttria-stabilised zirconia EB-PVD thermal barrier coating systems after CMAS attack - Boissonnet, Germain; Chalk, Christine; Nicholls, John R.; Bonnet, Gilles; Pedraza, Fernando (MDPI, 2020)
The impact of small deposits of calcium–magnesium–aluminium silicates (CMAS) on the top of thermal barrier coatings (TBCs) made of yttria-stabilised zirconia (YSZ) produced via electron-beam physical vapour deposition (EB-PVD) is shown to play a role in the microstructural and chemical stability of the coatings; hence, it also affects the thermal insulation potential of TBCs. Therefore, the present work investigates the degradation potential of minor CMAS deposits (from 0.25 to 5 mg·cm−2) annealed at 1250 °C for 1 h on a novel Er2O3-Y2O3 co-stabilised ZrO2 (ErYSZ) EB-PVD TBC, which is compared to the standard YSZ coating. Due to the higher reactivity of ErYSZ coatings with CMAS, its penetration is limited in comparison with the standard YSZ coatings, hence resulting in a better thermal insulation of the former after ageing.
Keywords: thermal barrier coatings (TBCs); electron-beam physical vapour deposition (EB-PVD); yttria-stabilised zirconia (YSZ); Erbia-yttria co-stabilised zirconia; thermal diffusivity